Sulfur infiltrated activated carbon cathodes for lithium sulfur cells: The combined effects of pore size distribution and electrolyte molarity - Lee, Jung Tae; Zhao, Youyang; Kim, Hyea; Cho, Won Il; Yushin, Gleb (ELSEVIER, 2014)
In this paper, we adopted three different commercial activated carbon samples (ACs) having different particle size, specific surface area and pore size to make sulfur carbon (S-AC) nanocomposites for rechargeable lithium sulfur batteries. The effect of the physical parameters of ACs and the combined effect of electrolyte molarity were investigated. The performance of the cells at two different temperatures of 25 and 70 degrees C were compared. For room temperature operation of the cells, the capacities of S infiltrated into microporous AC having smaller pore size and stronger interactions with sulfur and sulfides were lower than those of the S infiltrated into micro- and mesoporous ACs containing larger pores. In contrast, the microporous AC demonstrated higher capacity at the elevated temperature due to the improved ion transport rate. The effect of electrolyte molarity on the performance of Li/S cells was found to depend on the AC pore size and particle size distributions. Increasing electrolyte molarity from 1 to 3 M demonstrated improved cell performance and reduced polysulfide dissolution in all the studied S-AC samples. However, further increasing electrolyte salt concentration resulted in a high polarization and reduced cell performance in S-ACs having large particle size or smaller pores. (C) 2013 Elsevier B.V. All rights reserved.